2021
DOI: 10.36519/idcm.2021.74
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 among Healthcare Workers who were Exposed to COVID-19

Abstract: Background:We described the outcomes of healthcare workers (HCWs) who have been exposed to COVID-19. Materials and Methods:We included the HCWs exposed COVID-19 and admitted to the COVID-19 outpatient clinic between March 13 and August 31, 2020, at a university hospital in Ankara, Turkey. The clinical data and exposure status were retrospectively obtained from medical records. Results:We analyzed 809 admissions of 690 HCWs. In total, 490 HCWs were admitted after suspected exposure to COVID-19 patients. In 32% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Some studies have shown that the rate of household or community-acquired COVID-19 transmission is higher than that of hospital-acquired transmission (15,26). In the positive group, the rate of those with out-of-hospital contact was significantly higher than the negative group ( 95% vs 73.4% ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some studies have shown that the rate of household or community-acquired COVID-19 transmission is higher than that of hospital-acquired transmission (15,26). In the positive group, the rate of those with out-of-hospital contact was significantly higher than the negative group ( 95% vs 73.4% ).…”
Section: Discussionmentioning
confidence: 97%
“…While some studies reported no relationship between the transmission of COVID-19 and gender (13,14). Another study reported that male gender was an independent risk factor for transmission (15). Authors explained the higher incidence of disease in males by behavioural factors such as low handwashing rates and non-compliance with rules (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation